Mechanical Behavior of Concrete Reinforced with Waste Aluminium Strips - Imran Ali Channa; Abdullah Saand (Civil Engineering Journal, 2021)
The main objective of this research work is to investigate the influence of the addition of waste materials, like aluminium waste material, Soft Drink Tin Fibers (SDTF) or soft tins to improve mechanical properties of concrete and also study the strength behavior of concrete, such as flexural strength and indirect or split tensile strength. It has been acknowledged that the use of fibers in concrete has considerable effects to improve strength parameters and characteristics of concrete. In this research work, similar efforts are made to present the effects of soft tin fibers or aluminium waste material as a reinforcing material in concrete and to assess the mechanical behavior of concrete. Particularly, this research work aimed to investigate experimentally the effect of soft drink tins on tensile (cylinder splitting tensile strength) and flexural strength. Soft tin fibers of 25.4  5  0.5 mm in size were used and added from 1 to 5% by the weight of cement with the design mix of 1:1.624:2.760 at 0.50 w/c ratio. Therefore, 6 batches (every batch contained 3 prisms and 3 cylinders) were prepared and cast for evaluation of tensile and flexural strength. One batch was cast without inclusion of fibers (controlled batch) and remaining 5 batches were cast with the addition of fibers using 1, 2, 3, 4, and 5% respectively. It was revealed from obtained results that split tensile strength and flexural strength of specimen increases as compared to controlled batch up to 4% addition of fibers. Moreover, beyond 4% soft drink tin fiber level, strength begins to fall down. Thus, it can be suggested that mechanical properties of concrete can be enhanced by 4% of soft drink tin fibers. Moreover, in this study, soft drink tin fibers (SDTF) or aluminium waste are used as the application of utilization of waste materials as a partial construction material and also on another side it controls the solid waste and environmental pollution. Doi: 10.28991/cej-2021-03091718 Full Text: PDF